ANALISIS FIKIH MUAMALAH TERHADAP PRAKTIK SEWA-MENYEWA ULAR DI DESA KALIKAJAR, PURBALINGGA - Nisa, Ulfatul Khoirun (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
Ijarah is the act of selling benefits that is done by one person to another according to Islamic law. The pillars and conditions of ijarah include the contract (sighat al-aqad) that involves the offer and acceptance (ijab and kabul), the presence of two parties (aqid) involved in the transaction, the agreed fee (ujrah), and the benefit that is rented. The contract (akad) in ijarah is the meeting point of the offer and acceptance to reach an agreement. This research focuses on the practice of renting snakes in Kalikajar Village, Purbalingga, and analyzes it using the concept of fiqh muamalah. In this practice, there are some deviations from the principle of ijarah contract in Islam. Some conditions, such as wages and liability of the object of ijarah, are not met. This results in a lack of clarity regarding payment, rental time, and responsibility if the snake injures the renter. The research method used is field research with a qualitative method based on inductive analysis. Data were collected through observation, interviews, and documentation, and then analyzed with the concept of ijarah contract in fiqh muamalah. The results of the study show that the practice of renting snakes in Kalikajar Village Purbalingga is not valid because some conditions in the rental contract are not met. Thus, this study identifies deviations in this practice that are contrary to the principles of Islamic law. Keyword: Ekonomi, Muamalah dan Syari’ah